Velaglucerase alfa (VPRIV) enzyme replacement therapy in patients with Gaucher disease: Long-term data from phase III clinical trials - Hughes, Derralynn A (Am J Hematol, 2015)
Type 1 Gaucher disease is an inherited lysosomal enzyme deficiency with variable age of symptom onset. Common presenting signs include thrombocytopenia, anemia, hepatosplenomegaly, bone abnormalities, and, additionally in children, growth failure. Fifty-seven patients aged 3–62 years at the baseline of two phase III trials for velaglucerase alfa treatment were enrolled in the single extension study. In the extension, they received every-other-week velaglucerase alfa intravenous infusions for 1.2–4.8 years at 60 U/kg, although 10 patients experienced dose reduction. No patient experienced a drug-related serious adverse event or withdrew due to an adverse event. One patient died following a convulsion that was reported as unrelated to the study drug. Only one patient tested positive for anti-velaglucerase alfa antibodies. Combining the experience of the initial phase III trials and the extension study, significant improvements were observed in the first 24 months from baseline in hematology variables, organ volumes, plasma biomarkers, and, in adults, the lumbar spine bone mineral density Z-score. Improvements were maintained over longer-term treatment. Velaglucerase alfa had a good long-term safety and tolerability profile, and patients continued to respond clinically, which is consistent with the results of the extension study to the phase I/II trial of velaglucerase alfa. EudraCT number 2008-001965-27; http://www.clinicaltrials.gov identifier NCT00635427. Am. J. Hematol. 90:584–591, 2015. © 2015 Wiley Periodicals, Inc.